PERAN KEPALA SEKOLAH DALAM MENERAPKAN KEDISIPLINAN PESERTA DIDIK DI SDN 1 LIMBOTO KABUPATEN GORONTALO - Irmawati Duko Ishak; Yulanti S. Mooduto; Sri Wahyuni Antu (Jurnal Ilmu Pendidikan UMGo, 2024)
This research aims to determine the Principal's Role in Implementing Student Discipline at SDN 1 Limboto. This research uses a qualitative research type and uses a descriptive approach. The Principal’s Role in Implementing Student Discipline at SDN 1 Limboto is good. Indicators of school discipline include: having a record of attendance, giving awards to disciplined school members, having school rules, make school residents disciplined, and enforce the rules by providing fair sanctions for those who violate school rules. The role of the principal in implementing student discipline has been effective. The principal is sensitive to the environment, and can attend school every day so that can speak directly to all components of the school; the principal is a proactive leader.